Hydrologic Characterization of the Koshi Basin and the Impact of Climate Change - Bharati, Luna; Gurung, Pabitra; Jayakody, Priyantha (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Assessment of surface and groundwater resources and water availability for different sectors is a great challenge in Nepal mainly due to data limitations. In this study, the Soil Water Assessment Tool (SWAT) was used to simulate the hydrology and to calculate sub-basin wise water balances in the Koshi Basin, Nepal. The impacts of Climate Change (CC) projections from four GCMs (CNRM-CM3, CSIRO-Mk3.0,ECHam5 and MIROC 3.2) on the hydrology of the basin were also calculated. This paper summarizes some of the key results. The full report of the study is in preparation. The basin can be divided into the trans-mountain, central mountain, eastern mountain, eastern hill and central hill regions. Results show that current precipitation is highest in the central mountain and eastern mountain regions during both the dry and wet seasons. Water balance results showed that Actual ET as well as Runoff is also highest in the central and eastern mountain regions followed by the mid-hills. Results from climate change projections showed that average temperature will increase in the 2030’s by 0.7-0.9° Celsius. Results for 2030s projections also show that during the dry season, precipitation increases in the trans-mountain but decreases in the other regions for both A2 and B1 scenarios. During the wet season, the MarkSim projections show a decrease in precipitation in all the regions. Net water yields also increased for the trans-mountain zone during the dry season but show varying results during the monsoon. Assessment of projected future flow time series showed that there will be an increase in the number of extreme events; i.e., both low flows and large floods. There is however; a high degree of uncertainty in the projected climate data as the relative standard deviation was quite high. DOI: http://dx.doi.org/10.3126/hn.v11i1.7198 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.18-22